Productive Waqf Transformation: Integration of Islamic Historical Values and Sharia Economic Innovation - Muhamad Baharudin Yusuf; Khusnudin (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to investigate the evolution of productive waqf within the framework of Islamic history, along with the utilization of digital technology to facilitate sustainable financing in contemporary society. By integrating historical Islamic values exemplified by the waqf practices of Umar bin Khattab and Uthman bin Affan, this research assesses the modernization of waqf principles through the application of digital innovations, including blockchain technology and sharia-compliant crowdfunding. The methodology used in this research is qualitative and descriptive, emphasizing a comprehensive literature review of various Islamic historical texts combined with an analysis of advances in digital technology relevant to waqf management. The research findings show that the incorporation of technology into waqf administration, particularly through blockchain and digital platforms, has the potential to improve transparency, efficiency, and community engagement, while ensuring the sustainability and accountability of waqf resources. Nonetheless, challenges such as the digital literacy gap and the lack of standardized sharia regulations pose significant obstacles. This study advocates initiatives aimed at strengthening digital literacy and developing a policy framework that facilitates the implementation of digital waqf in accordance with Sharia principles, thereby maximizing the potential of waqf as an instrument of sustainable economic empowerment.